In vivo degeneration and the fate of inorganic nanoparticles. (10th February 2016) - Feliu, Neus; Docter, Dominic; Heine, Markus; del Pino, Pablo; Ashraf, Sumaira; Kolosnjaj-Tabi, Jelena; Macchiarini, Paolo; Nielsen, Peter; Alloyeau, Damien; Gazeau, Florence; Stauber, Roland H.; Parak, Wolfgang J.
Abstract : Nanoparticles comprise of a core, a surface coating, and a corona of adsorbed biomolecules, of which all parts can have a different fate. Abstract : What happens to inorganic nanoparticles (NPs), such as plasmonic gold or silver, superparamagnetic iron oxide, or fluorescent quantum dot NPs after they have been administrated to a living being? This review discusses the integrity, biodistribution, and fate of NPs after in vivo administration. The hybrid nature of the NPs is described, conceptually divided into the inorganic core, the engineered surface coating comprising of the ligand shell and optionally also bio-conjugates, and the corona of adsorbed biological molecules. Empirical evidence shows that all of these three compounds may degrade individually in vivo and can drastically modify the life cycle and biodistribution of the whole heterostructure. Thus, the NPs may be decomposed into different parts, whose biodistribution and fate would need to be analyzed individually. Multiple labeling and quantification strategies for such a purpose will be discussed. All reviewed data indicate that NPs in vivo should no longer be considered as homogeneous entities, but should be seen as inorganic/organic/biological nano-hybrids with complex and intricately linked distribution and degradation pathways.